Effects of ashwagandha root extract on physical performance - a clinical review - Karol Mazur; Marcin Lewicki; Dominika Mazur; Mateusz Tyniec; Agata Smoleń (Kazimierz Wielki University, 2021)
Sport is an important aspect of human life, affecting mental and physical health. Physical activity is one of the most effective ways of preventing the diseases of civilisation, such as coronary heart disease, hypertension, obesity and diabetes. There are many substances and methods that are used by athletes to improve physical performance, increase muscle mass and strength, increase concentration or suppress excessive emotions or reduce body weight to improve sports results. However, there is a need for research to find natural substances of plant origin, the use of which will lead to an increase in physical performance and will be fully legal and without side effects. Some scientists are conducting research into the use of ashwagandha root extract to improve physical performance. The aim of this study was to assess the efficacy and safety of ashwagandha root extract in the treatment of insomnia, anxiety and in reducing stress. Our study material consisted of publications, which were found in PubMed, ResearchGate and Google Scholar databases. In order to find the proper publications, the search has been conducted with the use of a combination of key words like: ''ashawagandha'', ''physical performance'', ''physical endurance'', ''muscle strength". The first step was to find proper publications from the last 15 years. The second step was to carry out an overview of the found publications.